Identifikasi nematoda usus pada feces balita di kelurahan Balang baru kota makassar - Nismawati nisma; Kesye Adolfina Jamngangun (Jurnal Media Laboran, 2020)
This study aims to see the presence or absence of worm eggs, especially the intestinal nematode group, because judging from the high prevalence of helminthiasis which is still widespread in Indonesia, especially at the age of toddlers, this research is very necessary. This research using qualitative descriptive method and laboratory approach requires a total sample of 10, the sample is taken by purposive sampling by looking at several existing criteria. Stool samples that have been taken are directly examined in the Laboratory of Health Analyst D3 Study Program, University of East Indonesia Makassar using a 2% eosin solution which is dropped on the feces on a glass object and observed on a microscope with 10x and 40x magnification. Interpretation of the results in percentage form and presented in a table, so that the results obtained were 1 positive sample of Ancylostoma duodenale (10%) and 9 negative samples of intestinal nematodes (90%). It was concluded that the role of parents, the influence of environmental hygiene, and children's personal hygiene greatly affect children's health, intestinal nematodes will enter and become infected when children are more likely to have direct contact with the outside world in this case often play on wet and loose soil surfaces.